Intraductal Oncocytic Papillary Neoplasm of the Pancreas: Report of a Case Requiring Completion Pancreatectomy - Wohlauer, Max V; McManus, Martine; Fukami, Norio; Gajdos, Csaba (JOP. Journal of the Pancreas, 2013)
Context Cystic tumors of the pancreas have been diagnosed with increasing frequency. Intraductal oncocytic papillary neoplasm is a rare type of cystic pancreatic tumor. Intraductal oncocytic papillary neoplasm is considered a distinct entity with the potential of developing into invasive carcinoma and it should be differentiated from other cystic tumors of the pancreas, including mucinous cystic neoplasm and other forms of intraductal papillary mucinous neoplasm (IPMN). Histologically, the formation of oncocytic cells and the complex morphology of the papillae distinguish intraductal oncocytic papillary neoplasm from IPMN. While the number of publications addressing the diagnosis, management and follow-up of patients with IPMN has been increasing, the behavior differences between IPMN and intraductal oncocytic papillary neoplasm have not been elucidated, secondary to very limited clinical experience. Case report Here, we are presenting a case of a patient with the diagnosis of intraductal oncocytic papillary neoplasm of the pancreas developing into invasive cancer. Conclusion This case stresses the necessity for lifelong surveillance of the remnant pancreas following partial pancreatectomy for intraductal oncocytic papillary neoplasm, due to the risk of developing multifocal disease. Image: PET CT image shows diffuse uptake of contrast in the head of the pancreas.